"Coaching" Queer: Hospitality and the Categorical Imperative of LGBTQ Asylum Seeking in Lebanon and Turkey. Issue 1 (1st June 2019) - Greatrick, Aydan
Abstract : This article argues that Northern responses to, and recognition of, LGBTQ refugees bind queer organizations in Lebanon and Turkey, which support such refugees, in a state of contradiction. This contradiction is defined both by the failure of Northern LGBTQ rights discourses to account for Southern ways of being queer, but also by the categorical imperative of hospitality, which asks that the "right" refugee appears in line with the moral, political, raced, and gendered assumptions of Northern host states. In recognizing this imperative, this article observes how queer organizations in Lebanon and Turkey navigate this contradiction by simultaneously "coaching" their beneficiaries on how to appear "credible" in line with Northern assumptions about sexual difference, while working to accommodate the alterity of those they support.